A nitrate photolysis source of tropospheric HONO is incompatible with current understanding of atmospheric chemistry - Rowlinson, Matthew; Carpenter, Lucy J.; Evans, Mat J.; Lee, James D.; Andersen, Simone T.; Sherwen, Tomas; Callaghan, Anna B.; Sommariva, Roberto; Bloss, William; Hou, Siqi; Crilley, Leigh R.; Pfeilsticker, Klaus; et al. (Atmospheric chemistry and physics, 2025)
Recent observations of nitrous acid (HONO) in the remote troposphere show much higher concentrations than can be explained through known sources, with important implications for air quality and climate. Laboratory evidence and modelling of field observations suggests that nitrate aerosol photolysis is the likely mechanism providing the additional HONO, offering a rapid route for recycling of NOx from nitric acid (HNO3). Previous studies of the global impact of this chemistry have used either very restricted HONO data or a “top-down” approach to parameterize the HONO source by reconciling simulated and observed NOx concentrations. Here, we use multiple, independent tropospheric HONO observations from different locations to parameterize nitrate photolysis, and evaluate its impacts on global atmospheric chemistry using GEOS-Chem. The simulations improve agreement between modelled and observed HONO concentrations relative to previous studies, decreasing the model bias by 5 %-20 %. The remaining (and large) underestimate of HONO in the model is due predominantly to an underestimate of total nitrate aerosol (−95 %) and is reduced to 20 % when accounting for low model nitrate. Despite the low bias in the model HONO, we find that nitrate aerosol photolysis leads to substantial global increases in NOx, O3 and OH concentrations, likely beyond the observational constraints. The additional source of NOx (∼ 48 Tg N yr−1 globally) is comparable to total NOx emissions from all sources (∼ 55 Tg yr−1). These HONO observations in the remote troposphere, thus imply a large uncertainty in the NOx budget and an incomplete understanding of atmospheric chemistry. Improved techniques to measure HONO at the low concentrations typical of remote areas, coupled with more measurements in these areas and improved process level understanding of nitrate photolysis are needed to provide quantitative assessment of its potentially global-scale atmospheric impacts.
Veröffentlicht: 27. November 2025
Gesehen am 29.01.2026